Influence of light and temperature on seed germination of Macroptilium lathyroides - de Souza Almeida da Silva, Márcia; Oscar Mitsuo Yamashita, Prof; Aparecida Bandini Rossi, Ana; Antonio Camillo de Carvalho, Marco; Concenço, Germani; Eustáquio de Sá, Marco (South American Journal of Basic Education, Technical and Technological, 2020)
Macroptilium lathyroides is a species of Fabaceae, native to the Guianas, Brazil and Paraguay family. It is a moderately frequent ruderal plant in almost the entire country, infesting mainly orchards, side of roads, lawns and vacant lots. Seeds were collected in soybean fields infested with this plant in Batayporã (MS). Were subsequently reproduced in greenhouse belonging UNEMAT - Alta Floresta - MT. We sought to evaluate the effect of light and temperature on seed germination capacity. For the assay, the seeds were subjected to the presence and absence of light in fixed temperatures 20, 25, 30, 35 and 40 ºC and alternating 15/25, 20/30, 25/35 and 25/40 ºC. The experimental design was completely randomized with four replicates of 25 seeds. Germinated seeds were counted daily, and at the end of 10 daysit was determined IVG, germination percentage, shoot length, root length and dry mass. Seeds of M. lathyroides complete the germination process rapidly and uniformly constant temperatures between 20 and 30 ºC, and alternating temperatures between 15/25, 20/30 and 25/35 ºC.Temperature of 40 ºC leads to delay in this process. The seeds of this species germinate in the presence and absence of light, and is therefore considered positive photoblastic "preferential".